Evaluating Industrial Policy Implementation In Indonesia: A Case Study of Law No. 3/2014 on Industry - Sugeng Bahagijo; Amirul Mustofa (Journal of Politica Governo, 2025)
This study aims to critically analyze and evaluate the implementation of Indonesia’s Law No. 3 of 2014 on Industry as a strategic policy instrument for national industrial development. Utilizing a qualitative research design with a document analysis method, the study assesses the law's effectiveness, efficiency, relevance, and sustainability in addressing pressing structural challenges particularly early deindustrialization, declining manufacturing competitiveness, and the persistently low added value of domestic industrial output. Although Law No. 3 of 2014 provides a robust normative and legal framework, its practical implementation has encountered significant constraints. These include weak inter-agency coordination, limited institutional capacity at the subnational level, insufficient policy alignment across sectors, and minimal integration of small and medium-sized enterprises (SMEs) into the national industrial ecosystem. Using Dunn’s (2003) public policy evaluation framework, the study finds that the law has yet to foster an inclusive, adaptive, and innovation-driven industrial environment. Moreover, policy outcomes remain fragmented and inconsistent with long-term industrialization goals. To address these gaps, the study recommends enhancing policy implementation through stronger cross-sectoral integration, capacity-building for regional industrial governance, increased investment in research and development, and the protection of strategic industries vital to national resilience. These efforts are essential to lift Indonesia out of the deindustrialization trap and position it toward achieving sustainable, high-value industrial transformation.